Non-invasive continuous blood pressure monitoring using the ClearSight system for pregnant women at high risks of post-partum hemorrhage: comparison with invasive blood pressure monitoring during cesarean section - Takuya Misugi; Takashi Juri; Koichi Suehiro; Kohei Kitada; Yasushi Kurihara; Mie Tahara; Akihiro Hamuro; Akemi Nakano; Masayasu Koyama; Takasi Mori; Daisuke Tachibana (Korean Society of Obstetrics and Gynecology, 2022)
Objective This study aimed to investigate the accuracy and precision of continuous, non-invasive blood pressure obtained using the ClearSight system by comparing it with invasive arterial blood pressure, and to assess the hemodynamic changes using invasive methods and the ClearSight system in patients undergoing cesarean section. Methods Arterial pressure was measured invasively with an intra-arterial catheter and non-invasively using the ClearSight system during cesarean section in patients with placenta previa or placenta accreta. Blood pressure measurements obtained using these two means were then compared. Results Total 1,277 blood pressure measurement pairs were collected from 21 patients. Under Bland-Altman analysis, the ClearSight system demonstrated an acceptable accuracy with a bias and standard deviation of 8.8±13.4 mmHg for systolic blood pressure, −6.3±7.1 mmHg for diastolic blood pressure, and −2.7±8.0 mmHg for median blood pressure. Cardiac index levels were significantly elevated during fetal delivery and 5 minutes after placental removal, and systemic vascular resistance index levels were significantly decreased during fetal delivery and 40 minutes after placental removal. Conclusion In patients undergoing cesarean section, the ClearSight system showed excellent accuracy and precision compared to that of the currently used invasive monitoring system.